Isländische Naturlyrik im 19. Jahrhundert – einige Streiflichter - Kreutzer, Gert (Folia Scandinavica Posnaniensia, 2007)
On the basis of selected poems by Hjabnar Jónsson fra Bólu, Bjami Thorarensen, Jónas Hallgrimsson, Jón Thoroddsen, Grimur Thomsen, Benedikt Gróndal, Pall Ólafsson, Steingrimur Thorsteinsson, Matthias Jochumsson, Kristjan Jónsson, Porsteinn Erlingsson, and Einar Benediktsson, this essay presents an overview of the themes and forms of 19th-century Icelandic naturę poetry. While characterizing each poefs uniąue perspective on naturę, it also attempts to find similarities that are shared between these Icelandic authors.